Relevansi Nilai Akhlak Peserta Didik dalam Ekstrakurikuler Pramuka Di MIN 3 Kebumen - Lulu Ainun Fadilah; Benny Kurniawan; Oky Ristya Trisnawati (IAINU Kebumen, 2022)
This study aims to determine the relevance of the moral values of students in scoutextracurricular activities at MIN 3 Kebumen. The research subjects were the principal, scoutcoaches, and students. The research uses a qualitative approach. The instruments used areobservation, interviews, and documentation. The data analysis technique uses data reduction,data presentation, and conclusion drawing. The results of this study (1) How is the relevance ofthe moral values of students in scout extracurricular activities at min 3 Kebumen: (a) theaccuracy of the targeting of scout extracurricular activities in relevating moral values, (b) theimplementation of scout extracurricular activities in relevating moral values